Experimental investigation of a new spiral wingtip - Siddiqui, Naseeb; Mohammed Aldheeb, Mohammed Abdulmalek; Asrar, Waqar; Sulaeman, Erwin (Embry-Riddle Aeronautical University, 2018)
Experiments on the relative merits and demerits of slotted wingtips mimicking a bird’s primary feathers have been performed. The real emargination length of feather tips, their flexibility and curved shapes during cruise are considered in the present study. The experiments were performed at a Reynolds number of 3.7 x 105 on a symmetric flat plate half wing of aspect ratio 3. Lift, drag and pitching moments were measured using a six component aerodynamic balance. Four different shapes inspired by bird primary feathers have been analysed. The rigid curved tip performed the best increasing the L/D ratio by 20%. This improvement has been compared with forty different wingtips model available in the literature which shows that rigid curved tip provide better L/D performance. Based on this improvement the key performance indicator of Jet and propeller airplane has been calculated that shows a 7.8% and 9% increase in range for propeller and Jet airplane, respectively.